2021
DOI: 10.1017/jfm.2021.85
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-geostrophic vortex solutions over isolated topography

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…The nonlinear origin of residual flows may explain the asymmetry of the persistent dipolar structures seen in figure 8(b,c). Interestingly, a similar asymmetry is characteristic of the nonlinear dipolar solutions of Gonzalez & Zavala Sansón (2021). We showed that some qualitative and quantitative features of the residual dipoles are congruent with the theoretical solutions.…”
Section: Long-term Residual Flowssupporting
confidence: 79%
See 4 more Smart Citations
“…The nonlinear origin of residual flows may explain the asymmetry of the persistent dipolar structures seen in figure 8(b,c). Interestingly, a similar asymmetry is characteristic of the nonlinear dipolar solutions of Gonzalez & Zavala Sansón (2021). We showed that some qualitative and quantitative features of the residual dipoles are congruent with the theoretical solutions.…”
Section: Long-term Residual Flowssupporting
confidence: 79%
“…Residual vortices are compatible with analytical solutions of barotropic flows over topography. Here we compare the asymmetric dipolar structures over the mountain, discussed in § 4.2.1, with nonlinear QG solutions recently derived by Gonzalez & Zavala Sansón (2021). The derivation is relatively simple but not trivial, so further details should be consulted in that paper.…”
Section: Quasi-geostrophic Analytical Solutions Of Asymmetric Dipolesmentioning
confidence: 94%
See 3 more Smart Citations